Demanda de torque e potência de implementos agrícolas acionados pela tomada de potência - Druzian, Eduardo Londero (2018)
The agricultural tractor is considered the modern agriculture basis due its versatility within a rural property. Many tests were needed to determine their ability to supply power to equipment, tools and other machines in agriculture. However, few studies present data on the demand for torque and power at the agricultural tractors power take-off (PTO). This research aims quantify this demand from experiments performed with mechanized sets, by using a thymocyte coupled between the agricultural tractor power take-off and the agricultural equipment cardanic tree, commonly used in agricultural activities located in Rio Grande do Sul state central region, in Brazil. The determinations were made following statistical experiments precepts, finding values of torque and rotation in the cardan shaft of the equipment in activation, but without displacement or execution of its specific purpose and energy consumption in different operating conditions. The results point to equipment with low torque and power demand, considering empty activity condition and the more severe work condition. They also point to equipment that demand a lot of torque and power through the power take-off. The highest energy demanding equipment was the rotating hoe, which, when working on surface ground slightly revolved with lightweight leveler grid, consumed 43.21 kW (58.75 cv). This and other equipment performance stands out the importance of considering the power provided by the tractor power take-off at the acquisition moment and for the mechanized set project.